Empowering MSMEs for Sustainable Growth in Timor-leste: A Community Engagement Perspective - Sunarjo, Wenti Ayu; Belo, Teresa Freitas; Murdianingsih, Dian; Khafid, Abdul; Rokhman, Nur (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are pivotal to economic diversification and inclusive growth in Timor-Leste, yet many still face barriers in finance, technology, and sustainability. This community service initiative aimed to strengthen MSME capacity through education, innovation, and participatory engagement between academia, government, and industry. Using a qualitative-descriptive approach within the community-based empowerment framework, the program integrated training in entrepreneurship, digital literacy, and green business practices. The implementation focused on cross-border collaboration between Timor-Leste and Indonesian MSMEs, particularly through the Kauman Batik Village Association in Pekalongan, as a model for cultural and creative entrepreneurship. Results showed a 73% improvement in participants’ understanding and skill levels, demonstrating the effectiveness of knowledge transfer and capacity-building methods. The project highlights that empowering MSMEs through collaborative community engagement can enhance competitiveness, foster sustainable practices, and promote cultural identity in global markets. Future initiatives are recommended to focus on digital transformation, financial inclusion, and eco-innovation